Commentary: The North in a Renewed Canada - Hill, Cynthia C. (ARCTIC, 1992)
On 22 January 1992, Cynthia Hill, Chair of the Arctic Institute Board of Directors, Board member Robert Blair and Executive Director Mike Robinson attended the hearings of the Special Joint Committee of the Senate and of the House of Commons on a Renewed Canada in Edmonton, Alberta. This federal committee was formed in September 1991 to review the Government of Canada's constitutional proposals set out in a discussion paper entitled Shaping Canada's Future Together. On behalf of the Arctic Institute of North America, Cynthia Hill presented the following statement to the committee.